Under the shadow of structural violence: Work and family dynamics for Latina farmworkers in southwestern Idaho - Som Castellano, Rebecca; Meierotto, Lisa; Curl, Cynthia (Journal of Agriculture, Food Systems, and Community Development, 2022)
Latina farmworkers play an essential role as agricultural laborers while at the same time managing responsibilities at home. However, little attention has been paid to these women’s lives, including how they manage the multiple roles they occupy. This is problematic in part because occupying multiple roles, particularly roles that may conflict with each other, can negatively influence well-being, including physical, mental, emotional, and economic well-being. In this research, we examine the work-family interface for Latina farmworkers, asking: What factors shape the experiences of Latina farmworkers as they navigate the work-family interface? Building from a broader multi-method and interdisciplinary study, this paper utilizes interview and focus group data to examine Latinas laboring in the agricultural fields of Idaho. Findings suggest that many supports in the work and family domains (e.g., supportive co-workers, friends, and family) can aid Latina farmworkers in fulfilling the various forms of labor they are responsible for. However, several family and work demands (e.g., single parenthood, difficult work hours and conditions) make it challenging for Latina farmworkers to fulfill the various forms of labor they are responsible for. Structural violence and intersectionality shape these women’s experiences with both supports and demands in the work and family domains. Relatedly, we find that organizational, community, and geographic contexts shape the experiences of Latina farmworkers in fulfilling labor in the public and private spheres. In particular, race and gender, immigration and documentation status, community organizations, and rurality all shape the navigation of the work-family interface for these farmworkers.